Assessments Regarding the Legal Status of Afghans Who are Irregular Migrants in Turkey - Sema Çörtoğlu Koca (Public and Private International Law Bulletin)
In this study, the legal statuses of Afghans who are irregular migrants in our country, due to the events in Afghanistan, have been explored. To begin with, it has been attempted to determine which of the international protection types such as refugee, conditional refugee and subsidiary protection statuses can or cannot be obtained, as well as the examples of judicial decisions. The international protection application procedure has also been discussed while making this determination. When the international protection applicants and international protection status holders in Turkey are examined, it is discovered that the majority of these groups are Afghans. The issues to be considered in the individual evaluations of the administration in terms of each applicant while granting international protection status are also discussed. Moreover, regarding the evaluations made in terms of the applicant, the decisions of the European Court of Human Rights and the Turkish court decisions are included. Our study has also evaluated whether Afghan citizens can get temporary protection status and immigrant status. Citizens of the Syrian Arab Republic who came to or crossed our borders from Syria for temporary protection as a result of the events in Syria have been granted temporary protection. In our study, the case in which it is possible to grant Afghan citizens temporary protection has been evaluated. Moreover, it has been discussed whether it is possible to grant immigrant status to Afghan citizens of Turkish origin in the past. Finally, in the study, the types of residence permit that Afghan citizens who are irregular immigrants in the country can obtain in order to legally reside in Turkey are mentioned.